Construction and identification of psychometric property self-regulated learning scale for university students - Muhammad Hidayat; Difa Ardiyanti; Siti Muthia Dinni (Jurnal Ilmiah Psikologi Terapan, 2022)
Previous studies state that self-regulated learning is a pivotal component in predicting students’ learning outcome. The present study aims to test the psychometric property of self-regulated learning scale to obtain a sound instrument. The procedure in this study included the scale construction, followed by psychometric property identification covering the content validity (using Aiken’s V and reliability test (Cronbach’s Alpha) of the data obtained from 203 respondents. The reliability coefficient of the final scale was 0.908, its discriminating power ranged between 0.307 and 0.626 with a mean score of 0.462. In other words, the self-regulated learning scale exhibit adequate psychometric property to measure university students’ self-regulated learning.